A sketch of Afitti phonology - Alex de Voogt (LibraryPress@UF, 2009)
Political conflict in the Sudan and the spread of Arabic are threatening Afitti, a North Eastern Sudanic language that has received relatively little scholarly attention. In addition to presenting original data on the language, this paper shows that Afitti is markedly different from Nyimang, its nearest linguistic neighbor, in respect to the absence of a third tone, the lack of a contrast between dentals and alveolars, the absence of distinctive vowel length, and its limited labialization.